If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + -2) = 2(6 + 5) Reorder the terms: 6(-2 + 2x) = 2(6 + 5) (-2 * 6 + 2x * 6) = 2(6 + 5) (-12 + 12x) = 2(6 + 5) Combine like terms: 6 + 5 = 11 -12 + 12x = 2(11) Multiply 2 * 11 -12 + 12x = 22 Solving -12 + 12x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 12x = 22 + 12 Combine like terms: -12 + 12 = 0 0 + 12x = 22 + 12 12x = 22 + 12 Combine like terms: 22 + 12 = 34 12x = 34 Divide each side by '12'. x = 2.833333333 Simplifying x = 2.833333333
| 6x=458.40 | | v-2.72=3.63 | | X+sqrt(x)=0 | | 14(t-6)+4t=6(3t+4)-11 | | 12/5=6x | | 3v-15=36 | | 9p-7p= | | 3(a-5)=-10 | | (1-1/n)(1-2/n) | | 0.25x^2-8x+64=0 | | 4y+4y=7y-1 | | 5(x+10)=40 | | 5(x-4)=3x-7 | | 36.90=9 | | x-3=-27 | | 9p-7p+4p-6p= | | 3x/4=9/2 | | 9y^2+54y+0=0 | | 9x+8=4x-3 | | -3=-27 | | -2(2x-4)+8x-4= | | -12=-3/4z | | 17q-14xq=11q | | 3x(t-3)=27 | | x/-11=5 | | F=9/5x+32 | | 9x-(2x-1)=37 | | 36/(2x)=6 | | 5+x=-22 | | 5(7b-6)=110 | | -2(5s-6)-12=-2(9s+4)-3 | | 36/2x=6 |